If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4-9x=1+3(4+x)
We move all terms to the left:
4-9x-(1+3(4+x))=0
We add all the numbers together, and all the variables
-9x-(1+3(x+4))+4=0
We calculate terms in parentheses: -(1+3(x+4)), so:We get rid of parentheses
1+3(x+4)
determiningTheFunctionDomain 3(x+4)+1
We multiply parentheses
3x+12+1
We add all the numbers together, and all the variables
3x+13
Back to the equation:
-(3x+13)
-9x-3x-13+4=0
We add all the numbers together, and all the variables
-12x-9=0
We move all terms containing x to the left, all other terms to the right
-12x=9
x=9/-12
x=-3/4
| 20x+1+22x-13=180 | | 198=-4x+-12x+6 | | 4x-5=2(2-1)-3 | | 1/5+r=-3/8 | | 11-3b=8 | | 1/4a12=5/4a+6 | | 5s-2=8+5s | | 1/5+r=-3/4 | | 78/65=x/100 | | 0.125(a+24)=10 | | 2+1.25f=10–2.75f | | 7/8k+7=9 | | s-36/8=5 | | p−31/6=−2/2 | | 2h=3=9 | | 4+2x=84+2x=8 | | 3f+8=17 | | 8=4u-4 | | -1/6v+16=0 | | 2/x+5=6 | | 12+2x=112+2x=1 | | 54x-8=12 | | 5+3x=8x+24 | | 3(x-6)-2=-4x+8 | | 3(x-2)+3=3(2x-8) | | 30=13u-7u | | 3s+9s+10s=16 | | 17x+4-3x=8-10x+44 | | 5=q-75/4 | | 3-(x-1)=25 | | 7d+d=4d-7=5d | | 41=3x+9 |